2008
DOI: 10.5194/bgd-5-841-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbiology and atmospheric processes: chemical interactions of Primary Biological Aerosols

Abstract: Abstract. This paper discusses the influence of bioaerosols on atmospheric chemistry and vice versa through microbiological and chemical properties and processes. Several studies have shown that biological matter represents a significant fraction of air particulate matter and hence affects the microstructure and water uptake of aerosol particles. Moreover, airborne micro-organisms can transform chemical constituents of the atmosphere by metabolic activity. Recent studies have emphasized the viability of bacter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 115 publications
0
5
0
1
Order By: Relevance
“…However, data on microorganisms associated with PM are scarce for Africa. Understanding both components of PM is crucial, as the relative harm of each component may differ by concentration or composition and the combination of both chemical and biological components may be more harmful than their individual components [12,39]. Evidence suggests that the composition of emissions is more important than merely controlling the absolute sources [33,40].…”
Section: Introductionmentioning
confidence: 99%
“…However, data on microorganisms associated with PM are scarce for Africa. Understanding both components of PM is crucial, as the relative harm of each component may differ by concentration or composition and the combination of both chemical and biological components may be more harmful than their individual components [12,39]. Evidence suggests that the composition of emissions is more important than merely controlling the absolute sources [33,40].…”
Section: Introductionmentioning
confidence: 99%
“…BCL was simulated in palmitic acid bilayers at pH 6 and pH < 4 as two different classes of lipase-binding lipids based on the differences in protonation states . Comparisons between these two sets of simulations also allows us to observe differences in dynamics of BCL as a function of aging in SSA particles ,, and relate these observations back to the change in surface areas witnessed from Langmuir isotherms. BCL is more dynamic in palmitic acid bilayers at a pH of <4 versus that at a pH of 6, likely due to protein instability in lower pH environments.…”
mentioning
confidence: 99%
“…The data obtained so far indicate that bioaerosols play an important role [ 6 , 11 , 27 , 28 ] in the physical and chemical processes occurring in the atmosphere [ 1 , 29 ]. It was shown that bioaerosols can bind to surrounding particles, thus influencing atmospheric processes by acting as condensation nuclei in clouds and initiating precipitation [ 10 , 30 , 31 ].…”
Section: The Main Properties Of Bioaerosolsmentioning
confidence: 99%